INNOVATIVE APPROACHES IN THE EARLY DETECTION AND MANAGEMENT OF CORONARY ARTERY DISEASE (Modern American Journal of Medical and Health Sciences, 2025)
Coronary artery disease (CAD) remains a leading cause of morbidity and mortality worldwide. Early detection and effective management are critical to improving patient outcomes and reducing healthcare burdens. This article explores the latest innovative approaches in diagnosing and treating CAD, including advancements in biomarker identification, non-invasive imaging technologies, and the application of artificial intelligence in risk stratification. Additionally, emerging therapeutic strategies such as personalized medicine and novel pharmacological agents are discussed. By integrating cutting-edge diagnostic tools with tailored management plans, healthcare providers can enhance early intervention, prevent disease progression, and improve quality of life for patients with CAD. This review highlights the potential of these innovations to transform clinical practice and offers insights into future research directions.